2017
DOI: 10.1136/bmj.j2376
|View full text |Cite|
|
Sign up to set email alerts
|

Serum uric acid levels and multiple health outcomes: umbrella review of evidence from observational studies, randomised controlled trials, and Mendelian randomisation studies

Abstract: Objective To map the diverse health outcomes associated with serum uric acid (SUA) levels. Design Umbrella review. Data sources Medline, Embase, Cochrane Database of Systematic Reviews, and screening of citations and references. Eligibility criteria Systematic reviews and meta-analyses of observational studies that examined associations between SUA level and health outcomes, meta-analyses of randomised controlled trials that investigated health outcomes related to SUA lowering treatment, and Mendelian randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
232
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(266 citation statements)
references
References 146 publications
(117 reference statements)
14
232
2
2
Order By: Relevance
“…A substantial body of work suggests that increased uric acid levels may independently regulate important aspects of metabolism and contribute to cardiometabolic risk (79)(80)(81)(82)(83). However, Mendelian randomization studies do not strongly support a causal role for circulating uric acid in mediating cardiometabolic disease (84). The association between uric acid levels and cardiometabolic risk may be indirect and may reflect activation of distinct fructoseregulated processes that contribute both to uric acid production and cardiometabolic risk.…”
Section: Genetic Lessons About Fructose Metabolismmentioning
confidence: 99%
“…A substantial body of work suggests that increased uric acid levels may independently regulate important aspects of metabolism and contribute to cardiometabolic risk (79)(80)(81)(82)(83). However, Mendelian randomization studies do not strongly support a causal role for circulating uric acid in mediating cardiometabolic disease (84). The association between uric acid levels and cardiometabolic risk may be indirect and may reflect activation of distinct fructoseregulated processes that contribute both to uric acid production and cardiometabolic risk.…”
Section: Genetic Lessons About Fructose Metabolismmentioning
confidence: 99%
“…In contrast, in recent meta-analysis lowering SUA levels under treatment did not predict improved surrogate clinical outcomes in HF [30]. Moreover, there was not convincing evidence regarding associations of SUA levels with increased risk of HF and other disease at higher risk of HF and HF mortality [31].…”
Section: Short Communicationmentioning
confidence: 90%
“…Second, does the increased prevalence of comorbidities in incident gout patients imply a pathogenic link between these conditions? A recent metaanalysis summarizing studies investigating the association between urate levels and comorbidities concluded that a causal role of urate levels linked to comorbidities such as diabetes, hypertension, metabolic syndrome, and renal diseases has not been demonstrated by Mendelian randomization study (which eliminates confounding using genetic tools) with sufficient evidence, despite a strong support from epidemiological studies 17 . Third, should gout patients with comorbidities be managed differently from those with "primary" gout?…”
Section: Rheumatologymentioning
confidence: 99%